THE EFFECT OF RATIONAL EMOTIONAL BEHAVIOR THERAPY (REBT) ON KNOWLEDGE ABOUT THE IMPACT OF EARLY MARRIAGE ONADOLESCENT GIRLS AT THE AL-KHOLAFIYAH ISLAMICBOARDING SCHOOL IN LUMAJANG - Nora Eflin Anggela; Yessy Nur Endah Sary; Muthmainah Zakiyyah (The Shine Cahaya Dunia Kebidanan, 2026)
Background: Early marriage among adolescent girls remains a serious health and social problem, driven in part by a lack of knowledge about its negative impacts. Rational Emotive Behavior Therapy (REBT) is an effective counseling approach for changing irrational thought patterns and increasing adolescents' understanding of the consequences of their actions. With this background, the researcher aimed to explore "The Effect of Rational Emotive Behavior Therapy (REBT) on Knowledge of the Impact of Early Marriage on Adolescent Girls at the Al-Kholafiyah Islamic Boarding School in Lumajang." Method: The research design is a plan or plan created by the researcher as a framework for the activities to be implemented. This study employed a cross-sectional design. The population in this study was all 32 adolescent girls at the Al-Kholafiyah Islamic Boarding School in Lumajang, aged 13-18. The sample size was all 32 adolescent girls at the Al-Kholafiyah Islamic Boarding School in Lumajang, aged 13-18. Results: The Wilcoxon statistical test results indicate a p-value of 0.00 with a significance level (α) <0.05. Because the p-value is less than α, H2 is rejected and H1 is accepted. This indicates that there is an effect of Rational Emotional Behavior Therapy (REBT) on knowledge about the impact of early marriage on adolescent girls at the Al-Kholafiyah Islamic Boarding School in Lumajang. Conclusion: The results of this study indicate that there is an effect of Rational Emotional Behavior Therapy (REBT) on knowledge about the impact of early marriage on adolescent girls at the Al-Kholafiyah Islamic Boarding School in Lumajang.